Robot di tempat kerja: Revolusi atau ancaman bagi tenaga kerja manusia? - Khoiriyah, Lailatul (Maliki Interdisciplinary Journal, 2024)
The use of robotic technology in the workplace has changed the industrial landscape significantly in the last few decades. This article explores whether the presence of robotics in the workplace represents a revolution that brings progress or instead poses a threat to the human workforce. By looking at the development of robotics in the manufacturing industry and service sector, we can understand how operational efficiency and productivity have increased thanks to the presence of robots. However, the replacement of human jobs by robots raises concerns about job losses and the social and economic impacts. This article also highlights the importance of re-education and skills development for the workforce to be able to compete in this digital era. In looking ahead, it is necessary to pay attention to how humans and robots can collaborate in harmony, as well as the need for appropriate regulations to ensure safety and fairness in the application of robotic technology. Thus, this article offers a comprehensive view of the implications of the use of robots in the workplace and the challenges that must be faced to achieve an inclusive and sustainable transformation.